Manajemen Kewirausahaan “Air Mineral” dalam Mengembangkan Kemandirian di Pondok Pesantren Sabilussalam Pasir Angin H. Latif Cibunigeulis Bungursari Kota Tasikmalaya - Miftah Hadiansyah Noor; Malik, Amarullah; Ade Ikbal Pauji (Program Studi Manajemen Pendidikan Islam, 2024)
Entrepreneurial management of Islamic Boarding Schools is a form of creative and innovative utilization of economic potential as a strategic step in community empowerment, and development of internal independence of institutions from an economic aspect so that they have self-supporting and self-financing capabilities. Sabilussalam Islamic Boarding School in Tasikmalaya City has implemented a 'mineral water' entrepreneurship program since 2021, as an effort to develop the internal independence of Islamic boarding schools. This study aims to describe and analyze the management of 'mineral water' entrepreneurship at Sabilussalam Islamic Boarding School in Tasikmalaya City, starting from the aspects of planning, implementation, and control of entrepreneurship to develop the independence of Islamic boarding schools. This study uses a qualitative method, with in-depth interviews, in-depth observations and documentation studies as data collection techniques used. The stages of data analysis techniques include data reduction, data display, conclusions and verification. As for the validity of the data, the researcher triangulated sources, methods, and time. The results of the study showed that, 1) planning to start an entrepreneurship program includes strengthening the vision and mission, sharpening the program's objectives and appointing a person in charge, recruiting operational staff, 2) implementation of the entrepreneurship program includes providing basic training for operational staff, 3) control is carried out through determining achievement indicators and periodic reports on the achievement of the entrepreneurship program and conducting discussions with the management of the Islamic boarding school to get input